2020
DOI: 10.3390/molecules25215057
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Molecular Docking, Antiapoptotic and Caspase-3 Inhibition of New 1,2,3-Triazole/Bis-2(1H)-Quinolinone Hybrids

Abstract: A series of novel 1,2,3-triazoles hybridized with two quinolin-2-ones, was designed and synthesized through click reactions. The structures of the synthesized compounds were elucidated by NMR, IR, and mass spectra in addition to elemental analysis. The synthesized compounds were assessed for their antiapoptotic activity in testis, as testicular torsion is the main cause of male infertility. This effect was studied in light of decreasing tissue damage induced by I/R in the testis of rats using N-acetylcysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Addi tionally, the target compounds 221a-d were synthesized, in very good yields, via the re action of 4-{[1-(2-oxo-1,2-dihydroquinolin-4-yl)-1H-1,2,3-triazol-4-yl]methoxy}benzalde hydes 222a-d [73] with acetophenone (Scheme 85). Aly et al [74] also reported that the synthesis of hybrids 228a-g through click chemistry which is a powerful tool for a quick, highly selective, and reliable access to a reaction product with high yields. The Aly et al [74] also reported that the synthesis of hybrids 228a-g through click chemistry which is a powerful tool for a quick, highly selective, and reliable access to a reaction product with high yields.…”
Section: Entrymentioning
confidence: 99%
See 3 more Smart Citations
“…Addi tionally, the target compounds 221a-d were synthesized, in very good yields, via the re action of 4-{[1-(2-oxo-1,2-dihydroquinolin-4-yl)-1H-1,2,3-triazol-4-yl]methoxy}benzalde hydes 222a-d [73] with acetophenone (Scheme 85). Aly et al [74] also reported that the synthesis of hybrids 228a-g through click chemistry which is a powerful tool for a quick, highly selective, and reliable access to a reaction product with high yields. The Aly et al [74] also reported that the synthesis of hybrids 228a-g through click chemistry which is a powerful tool for a quick, highly selective, and reliable access to a reaction product with high yields.…”
Section: Entrymentioning
confidence: 99%
“…Aly et al [74] also reported that the synthesis of hybrids 228a-g through click chemistry which is a powerful tool for a quick, highly selective, and reliable access to a reaction product with high yields. The Aly et al [74] also reported that the synthesis of hybrids 228a-g through click chemistry which is a powerful tool for a quick, highly selective, and reliable access to a reaction product with high yields. The Aly et al [74] also reported that the synthesis of hybrids 228a-g through click chemistry which is a powerful tool for a quick, highly selective, and reliable access to a reaction product with high yields.…”
Section: Entrymentioning
confidence: 99%
See 2 more Smart Citations
“…Caspase family of cysteine protease enzymes has been an intensely studied target in drug design for many years (Ghavami et al, 2009;Shalini et al, 2015). Among the identified 14 mammalian caspases caspase -2, -3, -6, -7, -8, -9, and -10 were described as apoptotic caspases (Aly et al, 2020;El-Sheref et al, 2020). Apoptotic caspases are classified based on the site and mechanism of action as initiator caspases (caspase-2, -8, -9, -10) and executioner caspases (caspase-3, -6, -7).…”
Section: Introductionmentioning
confidence: 99%